Nanoanalytical electron microscopy of events predisposing to mineralisation of turkey tendon - Klosowski,M; Carzaniga,R; Shefelbine,S; Porter,A; McComb,D (Scientific Reports, 2018)
The macro- and micro-structures of mineralised tissues hierarchy are well described and understood. However, investigation of their nanostructure is limited due to the intrinsic complexity of biological systems. Preceding transmission electron microscopy studies investigating mineralising tissues have not resolved fully the initial stages of mineral nucleation and growth within the collagen fibrils. In this study, analytical scanning transmission electron microscopy and electron energy-loss spectroscopy were employed to characterise the morphology, crystallinity and chemistry of the mineral at different stages of mineralization using a turkey tendon model. In the poorly mineralised regions, calcium ions associated with the collagen fibrils and ellipsoidal granules and larger clusters composed of amorphous calcium phosphate were detected. In the fully mineralised regions, the mineral had transformed into crystalline apatite with a plate-like morphology. A change in the nitrogen K-edge was observed and related to modifications of the functional groups associated with the mineralisation process. This transformation seen in the nitrogen K-edge might be an important step in maturation and mineralisation of collagen and lend fundamental insight into how tendon mineralises.